Court of Four Seasons at Night (Pacific Novelty Co.)
On verso: The Court is surrounded by a beautiful colonnade in each of the four corners of which are niches containing groups of statuary, "Spring," "Summer," "Autumn" and "Winter," by Furio Piccirilli, and representing the four seasons.